An update on the nutritional profiles of quinoa (Chenopodium quinoa Willd.), amaranth (Amaranthus spp.), and chia (Salvia hispanica L.), three key species with the potential to contribute to food security worldwide. Issue 12 (7th December 2022) - Olmos, Enrique; Roman‐Garcia, Inmaculada; Reguera, Maria; Mestanza, Camilo; Fernandez‐Garcia, Nieves
Abstract: One of the major challenges facing the world nowadays is to ensure enough access to healthy food for a growing population. Under this food scenario, it should be noted that increasing food production is as important as improving its nutritional quality. Thus, different agronomy research and innovation programs have pursued food security through the increase in the quantity and nutritional quality of plant‐based foods. One key aspect in this respect is to increase agrobiodiversity by expanding the cultivation of underutilized highly nutritious crops such as chia, quinoa, or amaranth. The outstanding nutritional value of these crops resides in the compositional characteristics of their seeds, which include the presence of significant levels (and a good balance) of proteins, essential amino acids, lipids, and other components such as phenols, minerals, fiber, or vitamins, all contributing to support nutritious diets that also has health benefits such as the prevention of cardiovascular diseases. All of them, chia, amaranth, and quinoa, are considered emerging crops outside their center of origin (which is mainly located in South America), and their cultivation has been expanded worldwide in the last decade. This review mainly highlights recent knowledge about the nutritional characteristics of these three Latin American crops, with the aim of providing an updated information regarding the compositional profiles of their seeds.